Preterm birth and PM2.5 in Puerto Rico: evidence from the PROTECT birth cohort - Kipruto Kirwa; Zlatan Feric; Justin Manjourides; Akram Alshawabekeh; Carmen Milagros Velez Vega; José F. Cordero; John D. Meeker; Helen H. Suh (BMC, 2021)
Abstract Background Preterm birth (PTB, birth before 37 weeks of gestation) has been associated with adverse health outcomes across the lifespan. Evidence on the association between PTB and prenatal exposure to air pollutants is inconsistent, and is especially lacking for ethnic/racial minority populations. Methods We obtained data on maternal characteristics and behaviors and PTB and other birth outcomes for women participating in the Puerto Rico Testsite for Exploring Contamination Threats (PROTECT) cohort, who lived in municipalities located along the North Coast of Puerto Rico. We assessed pre-natal PM2.5 exposures for each infant based on the nearest US Environmental Protection Agency monitor. We estimated prenatal phthalate exposures as the geometric mean of urinary measurements obtained during pregnancy. We then examined the association between PM2.5 and PTB using modified Poisson regression and assessed modification of the association by phthalate exposure levels and sociodemographic factors such as maternal age and infant gender. Results Among 1092 singleton births, 9.1% of infants were born preterm and 92.9% of mothers had at least a high school education. Mothers had a mean (standard deviation) age of 26.9 (5.5) years and a median (range) of 2.0 (1.0-8.0) pregnancies. Nearly all women were Hispanic white, black, or mixed race. Median (range) prenatal PM2.5 concentrations were 6.0 (3.1-19.8) μ g/m3. Median (interquartile range) prenatal phthalate levels were 14.9 (8.9-26.0) and 14.5 (8.4-26.0), respectively, for di-n-butyl phthalate (DBP) and di-isobutyl phthalate (DiBP). An interquartile range increase in PM2.5 was associated with a 1.2% (95% CI 0.4, 2.1%) higher risk of PTB. There was little difference in PTB risk in strata of infant sex, mother's age, family income, history of adverse birth outcome, parity, and pre-pregnancy body mass index. Pregnancy urinary phthalate metabolite levels did not modify the PM2.5-PTB association. Conclusion Among ethnic minority women in Puerto Rico, prenatal PM2.5 exposure is associated with a small but significant increase in risk of PTB.